Do Non‐exporting Plants Benefit from Exporting Peer Plants?. Issue 3 (28th November 2019) - Chun, Hyunbae; Hur, Jung; Son, Nyeong Seon; Yoon, Haeyeon
Abstract : This study examines indirect spillover effects at plant level within firms by analyzing the performance of non‐exporting plants with exporting peer plants by using Korean plant–firm matched data from 2007 to 2013. Our results show that there are no significant differences in growth between non‐exporting plants and their exporting peer plants in the same firms, whereas significant differences exist among non‐exporting plants depending on whether their peers export. This implies that exporting peer plants are important channels through which non‐exporting plants benefit within a firm.